Pengaruh Store Atmosphere, Location dan Service Quality Terhadap Kepuasan Pelanggan Di Griya Kupi Kota Lhokseumawe - Harahap, Sakinah Tul Marhamah; Edyansyah, T .; Ikramuddin, Ikramuddin Ikramuddin (Jurnal Visioner & Strategis, 2024)
This study examined the influence of store atmosphere, location, and service quality on customer satisfaction at Griya Kupi. Primary data were collected through questionnaires distributed to 114 respondents, selected using purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS software. The partial results indicated that store atmosphere, location, and service quality significantly affected customer satisfaction at Griya Kupi. Simultaneously, store atmosphere, location, and service quality significantly affected customer satisfaction at Griya Kupi. It is recommended that Griya Kupi continue to enhance service quality to ensure customer satisfaction and foster loyalty. Furthermore, future researchers are encouraged to explore additional variables to gain deeper insights into their relationship with customer satisfaction at Griya Kupi.  Keywords: Store Atmosphere, Location, Service Quality, Customer Satisfaction.